National Institutes of Health Career Development Awards for Cardiovascular Physician-Scientists: Recent Trends and Strategies for Success - Lindman, Brian R. (J Am Coll Cardiol, 2015)
Nurturing the development of cardiovascular physician-scientist investigators is critical for sustained progress in cardiovascular science and improving human health. The transition from an inexperienced trainee to an independent physician-scientist is a multifaceted process requiring a sustained commitment from the trainee, mentors, and institution. A cornerstone of this training process is a career development (K) award from the National Institutes of Health (NIH). These awards generally require 75% of the awardee’s professional effort devoted to research aims and diverse career development activities carried out in a mentored environment over a 5-year period. We report on recent success rates for obtaining NIH K awards, provide strategies for preparing a successful application and navigating the early career period for aspiring cardiovascular investigators, and offer cardiovascular division leadership perspectives regarding K awards in the current era. Our objective is to offer practical advice that will equip trainees considering an investigator path for success.